Current practices for treatment of respiratory syncytial virus and other non‐influenza respiratory viruses in high‐risk patient populations: a survey of institutions in the Midwestern Respiratory Virus Collaborative. Issue 2 (29th March 2016) - Beaird, O.E.; Freifeld, A.; Ison, M.G.; Lawrence, S.J.; Theodoropoulos, N.; Clark, N.M.; Razonable, R.R.; Alangaden, G.; Miller, R.; Smith, J.; Young, J.A.H.; Hawkinson, D.; et al.
Abstract: Background: The optimal treatment for respiratory syncytial virus (RSV) infection in adult immunocompromised patients is unknown. We assessed the management of RSV and other non‐influenza respiratory viruses in Midwestern transplant centers. Methods: A survey assessing strategies for RSV and other non‐influenza respiratory viral infections was sent to 13 centers. Results: Multiplex polymerase chain reaction assay was used for diagnosis in 11/12 centers. Eight of 12 centers used inhaled ribavirin (RBV) in some patient populations. Barriers included cost, safety, lack of evidence, and inconvenience. Six of 12 used intravenous immunoglobulin (IVIG), mostly in combination with RBV. Inhaled RBV was used more than oral, and in the post‐stem cell transplant population, patients with lower respiratory tract infection (LRTI), graft‐versus‐host disease, and more recent transplantation were treated at higher rates. Ten centers had experience with lung transplant patients; all used either oral or inhaled RBV for LRTI, 6/10 treated upper respiratory tract infection (URTI). No center treated non‐lung solid organ transplant (SOT) recipients with URTI; 7/11 would use oral or inhaled RBV in the same group with LRTI. Patients with hematologic malignancy without hematopoietic stem cell transplantation were treated with RBV at a similar frequency to non‐lung SOT recipients. Three of 12 centers, in severe cases, treated parainfluenza and metapneumovirus, and 1/12 treated coronavirus. Conclusions: Treatment of RSV in immunocompromised patients varied greatly. While most centers treat LRTI, treatment of URTI was variable. No consensus was found regarding the use of oral versus inhaled RBV, or the use of IVIG. The presence of such heterogeneity demonstrates the need for further studies defining optimal treatment of RSV in immunocompromised hosts.